2014
DOI: 10.2478/aoas-2013-0062
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of carcass traits in ducks from a crossbred population

Abstract: The aim of this study was to estimate coefficients of heritability as well as genetic and phenotypic correlations among body weight and carcass traits. The dataset contained records of 387 birds from the second crossbred generation. The following traits were recorded: body weight (BW) at 11 weeks, carcass weight (CW), breast muscle weight including superficial and deep muscle (BMW), leg muscle weight including thigh and shank (LMW), wings weight (WW), skin with subcutaneous fat weight (SW), abdominal fat weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
3
6
0
Order By: Relevance
“…The present study is a continuation of earlier works by Mucha et al (2014aMucha et al ( , 2014b and Moliński et al (2015) with the same experimental material. It should be mentioned that the parental lines A-55 (Pekin-type ducks of Polish origin) and GL-30 (Pekin-type ducks of French origin) are conventionally used in Poland for production of commercial hybrids (A-55 x F-11, A-55 x P-55, A-55 x P-44 and GL-50 x GL-30) intended for intensive rearing of meat ducks (Wencek et al, 2015).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…The present study is a continuation of earlier works by Mucha et al (2014aMucha et al ( , 2014b and Moliński et al (2015) with the same experimental material. It should be mentioned that the parental lines A-55 (Pekin-type ducks of Polish origin) and GL-30 (Pekin-type ducks of French origin) are conventionally used in Poland for production of commercial hybrids (A-55 x F-11, A-55 x P-55, A-55 x P-44 and GL-50 x GL-30) intended for intensive rearing of meat ducks (Wencek et al, 2015).…”
Section: Introductionsupporting
confidence: 65%
“…The duck hybrids evaluated here were characterized by excellent meat performance traits (Mucha et al 2014a). The private sire alleles in three of the identified loci seem to be a promising element in further genetic improvement programs.…”
Section: Successful Identification Of Duck Genome Region Determining mentioning
confidence: 96%
“…The LW values achieved from the research were in line with the reported LW of some other researches (Leeson and Summer, 1982;Kinizetova et al, 1991), also found to be higher than LW reported by some researchers (Sainsbury, 1980;Isguzar, 2006;Ahaotu and Agbasu, 2015) and also lower than some others (Jones and Dawkins, 2010;Holderread, 2011;Mucha et al, 2014;Steczny et al, 2017).…”
Section: Resultssupporting
confidence: 90%
“…It has been reported that with a 5.19 ducklings m -2 stocking density at 48 days of slaughter age, mortality (M) was found as 5.20 %, mean live weight (MLW) was found as 3.35 kg and live weight gain LWG was found as 60.3 -81.3 g day -1 and total live weight (TLW) was found as 17.2 kg m -2 (Jones and Dawkins, 2010). From the findings of another research it was told that with a SD of 6 ducklings m -2 and in a growing period of 4 to 11 weeks, final live weight (FLW) was reported to be 3 111 g (Mucha et al, 2014). In another research where a SD of 6.7 ducklings m -2 was used, the LW of 57.5 g increased up to 3 518 g in males and 3 433 g in females giving a mean of 3 476 g in 49 days achieving an FCR of 2.47, feed consumption of 8.24 kg and a LWG of 69.9 g day -1 (Steczny et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Duck parts are currently a growing poultry market segment because consumers are willing to pay more for fresh or frozen breast fillets and hind-or forequarter rather than buying cheaper whole carcasses. Raw meat preparations are generally bought by consumers based on overall appearance, with special consideration of colour and drip loss (Makała and Olkiewicz, 2004;Mucha et al, 2014;Moliński et al, 2015).…”
Section: Introductionmentioning
confidence: 99%